American Manufacturing Unions' Stasis: A Paradigmatic Perspective - Murray, Alan I.; Reshef, Yonatan (Academy of Management Review, 1988)
This paper argues that American manufacturing unions, if they are to revitalize themselves numerically and politically, must develop new strategies in order to cope with rapidly changing environments. After reviewing two action paradigms that are available for unions, we show why manufacturing unions have adopted the economic rather than political paradigm. We argue that the economic paradigm is viable only under a specific set of conditions that no longer apply. Finally, long-term adherence to the economic paradigm produces resistance to paradigmatic change in response to external changes in many unions. As an illustration, we use the American auto industry.